8=n-2/9

Simple and best practice solution for 8=n-2/9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8=n-2/9 equation:



8=n-2/9
We move all terms to the left:
8-(n-2/9)=0
We add all the numbers together, and all the variables
-(+n-2/9)+8=0
We get rid of parentheses
-n+8+2/9=0
We multiply all the terms by the denominator
-n*9+2+8*9=0
We add all the numbers together, and all the variables
-n*9+74=0
Wy multiply elements
-9n+74=0
We move all terms containing n to the left, all other terms to the right
-9n=-74
n=-74/-9
n=8+2/9

See similar equations:

| p/3+36=41 | | -2|(y-4)/(5)|=-10 | | 6a+7-6a=13 | | 5d+23=78 | | 10b-7=32 | | 7g-10=5g | | x-0.7=0.3x | | 3x+2+4x+13+10x-33=180 | | 6=3s-9 | | 57.7x+280=5600+-222.3x | | 22-2w=2 | | 13=z/3+11 | | -63=7(h-95) | | 5x(x+7)=14x-7 | | 3/5x+7=13/5 | | 15.83b-4.6=5.95 | | d-57/10=3 | | -30c=-9c-3 | | 6x^2-7=-69 | | 3x+3/8=4x3/8- | | 8(u-92)=24 | | 2k^2+12k=-10 | | 2=f/9 | | 12.97-12q=17.11-11.4q | | 3n+11=-4(n-1) | | -8y^2-48=0 | | 8(f+93)=-8 | | 6x=11/8 | | 6m=5.75 | | 2x.3-x=x.15-4.5 | | 5+n=59 | | 90=6(t+7) |

Equations solver categories